Isolating membrane, preparation method thereof, and related secondary battery and electric device

CN119325666APending Publication Date: 2025-01-17CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380045749.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-02-13
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing secondary battery isolation films easily cause active ions to precipitate into dendrites during the charge and discharge process, which increases the risk of dendrites puncturing the isolation film, which in turn leads to internal short circuits and reduced safety performance of the secondary battery.

Method used

The combination of a porous substrate and high dielectric constant ferroelectric ceramic particles is used to regulate the electric field distribution through the ferroelectric effect, reducing the risk of active ion precipitation, and by uniformly distributing the ferroelectric ceramic particles in the porous substrate to reduce dendrite formation and side effects. reaction to improve the air permeability and mechanical properties of the isolation membrane.

Benefits of technology

It effectively reduces the risk of lithium dendrite formation and puncture, improves the safety performance, capacity performance and cycle performance of secondary batteries, and enhances the heat resistance and mechanical strength of the isolation film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119325666A_ABST
    Figure CN119325666A_ABST
Patent Text Reader

Abstract

The invention provides an isolating membrane, a preparation method of the isolating membrane, a related secondary battery and a related electric device. The isolating membrane comprises a porous base material and ferroelectric ceramic particles, the porous base material comprises a first area and a second area which are arranged in the thickness direction of the isolating membrane, and the ferroelectric ceramic particles are dispersed in the first area. The isolating membrane disclosed by the invention is relatively good in performance, and when the isolating membrane is applied to the secondary battery, the safety performance, the cycle performance and the like of the secondary battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Separator, preparation method thereof, and related secondary battery and electrical device Technical Field

[0001] The present application relates to the field of batteries, and in particular to an isolation membrane, a preparation method thereof, and related secondary batteries and electrical devices. Background Art

[0002] Secondary batteries have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes, and power tools, etc.

[0003] As battery applications expand, the performance requirements for secondary batteries are becoming increasingly stringent. To improve secondary battery performance, optimization and improvement of the separators within them are common. However, current separators offer excellent performance, and their application in secondary batteries improves safety and cycle performance.

[0004] Summary of the Invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a separator, a preparation method thereof, and related secondary batteries and electrical devices.

[0006] A first aspect of the present application provides an isolation membrane, which includes a porous substrate and ferroelectric ceramic particles. The porous substrate includes a first region and a second region arranged along the thickness direction of the isolation membrane, and the ferroelectric ceramic particles are dispersed in the first region.

[0007] Therefore, when the separator of the present application is applied to a secondary battery, on the one hand, during the charging process of the secondary battery, there is an internal electric field between the positive electrode and the negative electrode. Under the action of the internal electric field, the positive and negative charge centers inside the ferroelectric particles may be stimulated to shift, generating a reverse electric field. The reverse electric field can polarize the separator and promote the accelerated movement of active ions, thereby reducing the concentration gradient of active ions near the negative electrode current collector, that is, reducing the concentration of active ions on the side of the separator close to the negative electrode, and reducing the risk of active ions precipitating as dendrites. On the other hand, the active ions are precipitated as metals. The local volume expansion during the metal deposition process causes stress concentration. The first area where the ferroelectric ceramic particles are located may be deformed, resulting in instantaneous positive and negative charges on both sides of the separator thickness direction. Since the active ions carry positive charges, the electric field formed by the positive charges accumulated on one side of the separator repels the active ions from continuing to deposit at the stress concentration position, and the electric field formed by the negative charges accumulated on the other side (close to the negative electrode) attracts the active ions to deposit at this position, thereby changing the direction of dendrite growth. Taking lithium ions as an example, when lithium ions are deposited on the surface of the negative electrode, they accumulate charge, leading to a localized concentration of charge and the formation of a strong electric field, which in turn makes it easier for lithium ions in that area to form protruding dendrites. However, when the ferroelectric ceramic particles are subjected to an external electric field, they form a reverse electric field, which stops the further concentration of charge and alleviates the uneven charge distribution, thereby inhibiting the formation of dendrites. In other words, the risk of lithium ion precipitation is reduced, which can reduce the risk of lithium dendrites forming, thereby reducing the risk of lithium dendrites piercing the separator and causing internal short circuits in the secondary battery, thereby improving the safety performance of the secondary battery.

[0008] In some embodiments, the dielectric constant of the ferroelectric ceramic particles is ε, and the ferroelectric ceramic particles satisfy: 200≤ε≤3640.

[0009] Therefore, the dielectric constant of the ferroelectric ceramic particles of the present application is relatively high, which is conducive to the ferroelectric effect of the ferroelectric ceramic particles, and can improve the electric field distribution at the isolation membrane to a greater extent, thereby improving the metal deposition morphology, reducing the risk of positive and negative electrode short circuit caused by dendrite formation, and improving the safety performance of the secondary battery.

[0010] In some embodiments, the ferroelectric ceramic particles include one or more of perovskite structure compounds, tungsten bronze structure compounds, pyrochlore structure compounds and layered bismuth oxide structure compounds; the above materials have excellent ferroelectric effect, and under the action of an external electric field, they can undergo spontaneous polarization and generate a reverse electric field, which can accelerate the migration rate of active ions near the negative electrode plate and reduce the risk of dendrite formation, thereby reducing the risk of dendrites piercing the isolation membrane and causing internal short circuit of the secondary battery, further improving the safety performance of the secondary battery.

[0011] In some embodiments, the perovskite structure-based compound includes one or more of a titanate, a ferrite, and a niobate.

[0012] In some embodiments, the titanate includes one or more of barium titanate (BaTiO 3 ), lead titanate (PbTiO 3 ), and strontium titanate (SrTiO 3 ).

[0013] In some embodiments, the ferrite includes one or more of bismuth ferrite BiFeO 3 , lanthanum ferrite LaFeO 3 , and strontium ferrite SrFeO 3 .

[0014] In some embodiments, the tungsten bronze structured compound includes lead niobate PbNb2O6, barium sodium niobate Ba2NaNb5O 15 , barium strontium niobate Sr 1-x Ba x Nb2O6, lead bismuth niobate PbBiNb5O 15 and lead titanium niobate Pb3TiNb4O 15 One or more of , where 0<x<1.

[0015] In some embodiments, the pyrochlore structure compound includes one or more of cadmium pyrotantalate Cd2Ta2O7, lead pyroniobate Pb2Nb2O7, cadmium pyroniobate Cd2Nb2O7, gadolinium pyroniobate Gd2Nb2O7, and bismuth ruthenate Bi2Ru2O7.

[0016] In some embodiments, the layered bismuth oxide structured compound comprises bismuth titanate Bi4Ti3O 12 , lead bismuth niobate PbBi2Nb2O9, bismuth titanium niobate Bi3TiNbO9 and bismuth strontium titanate SrBi4Ti4O 15 One or more of .

[0017] In some embodiments, the volume distribution particle size Dv50 of the ferroelectric ceramic particles is D, with a unit of μm, and the ferroelectric ceramic particles satisfy: 0.05≤D≤5.00; optionally, 0.05≤D≤1.00.

[0018] Therefore, when the volume distribution particle size of the ferroelectric ceramic particles of the present application meets the above-mentioned range, the ferroelectric ceramic particles are not easy to clog the pores of the porous substrate, thereby improving the overall air permeability of the isolation membrane, ensuring the ion conduction channel, and improving the capacity performance and cycle performance of the secondary battery; and the particle size of the ferroelectric ceramic particles will not be too large, and the dispersion in the first region will be more uniform. The distribution density of the ferroelectric ceramic particles can be relatively high, which is conducive to better exerting the ferroelectric effect; and it is conducive to reducing the thickness of the first region, and can reduce the overall thickness of the isolation membrane; and the distribution density of the ferroelectric ceramic particles can be relatively high, which is conducive to better exerting the ferroelectric effect and further improving the capacity performance and cycle performance of the secondary battery.

[0019] In some embodiments, the porous substrate includes one or more of polyolefin polymers, polyamide, polyester, polysulfone and polyethersulfone; alternatively, the polyolefin polymer includes one or more of polyethylene, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl chloride, polypropylene and poly-1-butene.

[0020] In some embodiments, the porous substrate comprises a polymer having a number average molecular weight of 5×10 4 to 5×10 6 ; Optional 1×10 5 to 1×10 6 When the number average molecular weight of the polymer is within the above range, it has a relatively high viscosity and good adhesion to the ferroelectric ceramic particles, and the ferroelectric ceramic particles are not easily separated from the porous substrate.

[0021] In some embodiments, the thickness of the second region is H1, in μm; the thickness of the first region is H2, in μm, and the isolation film satisfies: 0.8≤H2 / 2H1≤3; optionally, 0.8≤H2 / 2H1≤2.

[0022] In some embodiments, 2.5≤H1≤4.5; and / or 3.5≤H2≤7.5.

[0023] Therefore, when the thickness of the second region and the first region of the present application meets the above range, the distribution thickness of the ferroelectric ceramic particles can be increased, thereby improving the ferroelectric effect of the ferroelectric ceramic particles.

[0024] In some embodiments, the thickness of the isolation membrane is H, in μm, and the isolation membrane satisfies: 5≤H≤25; optionally, 10≤H≤15. When the thickness of the isolation membrane is within the above range, the mechanical properties of the isolation membrane 7 can be further improved.

[0025] In some embodiments, the porosity of the separator is P%, 50≤P≤70. When the porosity of the separator is within the above range, it is beneficial to reduce ionic resistance, and active ions can migrate smoothly, thereby facilitating the capacity of the secondary battery.

[0026] In some embodiments, the air permeability of the separator is MAP, which is expressed in s / 100 mL, and 80≤MAP≤200. When the air permeability of the separator is within the above range, it is beneficial to reduce ionic resistance, allowing active ions to migrate smoothly, thereby facilitating the capacity of the secondary battery.

[0027] In some embodiments, the mass percentage of the ferroelectric ceramic particles based on the total mass of the separator is recorded as m1%, with 1≤m1≤15; and / or the mass percentage of the porous substrate based on the total mass of the separator is recorded as m2%, with 85≤m2≤99. When the mass percentage of the ferroelectric ceramic particles is within the above ranges, the overall ferroelectric effect of the separator can be enhanced, thereby further improving the safety and cycle performance of the secondary battery.

[0028] In some embodiments, two second regions are provided, and the first region is located between the two second regions.

[0029] As a result, the ferroelectric ceramic particles are dispersed in the first region, and the second region is provided on both sides of the first region, which is equivalent to the ferroelectric ceramic particles being wrapped by the second region; when the isolation membrane is applied to the secondary battery, the ferroelectric ceramic particles are not easily in contact with the positive electrode active material and / or the negative electrode active material, thereby reducing the risk of side reactions between the ferroelectric ceramic particles and the positive electrode active material and / or the negative electrode active material, reducing the loss of the positive electrode active material and / or the negative electrode active material, and ensuring the capacity performance and cycle performance of the secondary battery.

[0030] The second aspect of the present application also provides a method for preparing an isolation membrane, comprising: providing a supporting mixed material, the supporting mixed material including a first polymer; mixing a second polymer and ferroelectric ceramic particles into a functional mixed material; heat treating the supporting mixed material to melt the first polymer and form a supporting melt; heat treating the functional mixed material to melt the second polymer and form a functional melt; setting the supporting melt on at least one side of the functional melt, and jointly extruding the supporting melt and the functional melt, and then stretching and solidifying to form an isolation membrane.

[0031] In some embodiments, the supporting hybrid material further comprises a porogen; and / or the functional hybrid material further comprises a porogen.

[0032] The third aspect of the present application further provides a secondary battery, comprising an isolation membrane according to any embodiment of the first aspect of the present application or an isolation membrane obtained by the preparation method according to any embodiment of the second aspect of the present application.

[0033] The fourth aspect of the present application further provides an electrical device, comprising a secondary battery as described in the embodiment of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0035] FIG1 is a schematic diagram of an isolation film according to an embodiment of the present application.

[0036] FIG. 2 is a schematic diagram of an embodiment of a secondary battery of the present application.

[0037] FIG. 3 is an exploded schematic diagram of the embodiment of the secondary battery of FIG. 2 .

[0038] FIG4 is a schematic diagram of an embodiment of a battery module of the present application.

[0039] FIG5 is a schematic diagram of an embodiment of a battery pack of the present application.

[0040] FIG. 6 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 5 .

[0041] FIG. 7 is a schematic diagram of an embodiment of an electric device including the secondary battery of the present application as a power source.

[0042] FIG8 is a scanning electron microscope image of the isolation film of Example 1 of the present application;

[0043] FIG9 is a second scanning electron microscope image of the isolation film of Example 1 of the present application;

[0044] FIG10 is a scanning electron microscope image of the isolation film of Comparative Example 2 of the present application.

[0045] The drawings are not necessarily drawn to scale.

[0046] The following are the descriptions of the reference numerals:

[0047] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;

[0048] 5. Secondary battery; 51. Housing; 52. Electrode assembly;

[0049] 53. Cover plate;

[0050] 6. Electrical devices;

[0051] 7. Isolation membrane; 70. Porous substrate; 71. Second region; 72. First region; 73. Ferroelectric ceramic particles. DETAILED DESCRIPTION

[0052] The following detailed description specifically discloses the embodiments of the separator, its preparation method, and related secondary batteries and electrical devices of the present application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid unnecessary length in the following description and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0053] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0054] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0055] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.

[0056] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.

[0057] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0058] In this application, the terms "plurality" and "multiple" refer to two or more.

[0059] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.

[0060] Unless otherwise stated, the numerical values ​​of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application.

[0061] Typically, a secondary battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet. Its main function is to prevent the positive electrode sheet and the negative electrode sheet from short-circuiting, while allowing active ions to pass freely to form a loop.

[0062] With the application and promotion of secondary batteries, people have increasingly higher requirements for secondary battery safety performance. During the charge and discharge process of secondary batteries, active ions such as lithium ions and sodium ions easily form dendrites on the surface of the negative electrode. The growth of dendrites may puncture the separator and cause a short circuit between the positive and negative electrodes, thus posing a safety risk to the secondary battery.

[0063] The inventors have found that improving the performance of the isolation membrane is an effective measure to improve the safety performance of secondary batteries. In related technologies, a functional coating is provided on the substrate of the isolation membrane in the hope of improving the mechanical properties of the isolation membrane, thereby reducing the risk of dendrites piercing the isolation membrane; however, after further research, the inventors found that there is a large interface impedance between the functional coating and the substrate, which is not conducive to the migration of active ions between the positive electrode and the negative electrode, and the functional coating may be in direct contact with the positive and negative electrodes, so that the functional coating may react with the positive and negative electrodes to cause loss of active materials in the positive and negative electrodes, thereby reducing the capacity and cycle performance of the secondary battery; therefore, it is difficult for secondary batteries to take into account both improving safety performance and cycle performance.

[0064] In response to the above problems, the inventors proposed an isolation membrane, improved the structure and material of the isolation membrane, and dispersed ferroelectric ceramic materials in the substrate, so that the ferroelectric ceramic materials in the isolation membrane can regulate the electric field in the secondary battery, reduce the risk of active ion precipitation and dendrite formation, and under the protection of the substrate, the ferroelectric ceramic materials are not easy to react with the positive electrode active material and / or the negative electrode active material, thereby improving the safety performance, dynamic performance, capacity performance and cycle performance of the secondary battery using the isolation membrane.

[0065] Isolation film

[0066] In a first aspect, the present application provides an isolation membrane.

[0067] As shown in Figure 1, the isolation membrane 7 includes a porous substrate 70 and ferroelectric ceramic particles 73. The porous substrate 70 includes a first region 72 and a second region 71 arranged along the thickness direction of the isolation membrane 7, and the ferroelectric ceramic particles 73 are dispersed in the first region 72. In the embodiment of the present application, the second region 71 is arranged on at least one side of the first region 72, that is, the second region 71 can be arranged on one side of the first region 72, or on both sides of the first region 72.

[0068] Although the mechanism is not yet clear, the inventors have found that the separator 7 of the present application, when applied to a secondary battery, can improve the safety performance, dynamic performance, capacity performance, and cycle performance of the secondary battery.

[0069] The inventors speculate that the mechanism of action is as follows:

[0070] First, the ferroelectric ceramic particles 73 have a ferroelectric effect, which allows them to undergo spontaneous polarization under the action of an external electric field, generating a reverse electric field, which can accelerate the migration rate of active ions near the negative electrode plate and reduce the risk of dendrite formation, thereby reducing the risk of dendrites piercing the isolation membrane 7 and causing internal short circuit of the secondary battery, thereby improving the safety performance of the secondary battery.

[0071] Specifically, on the one hand, when the separator 7 is applied to a secondary battery, during the charging process of the secondary battery, an internal electric field exists between the positive and negative electrode sheets. Under the action of the internal electric field, the positive and negative charge centers inside the ferroelectric particles may be stimulated to shift, generating a reverse electric field. The reverse electric field can polarize the separator 7 and promote the accelerated movement of active ions, thereby reducing the concentration gradient of active ions near the negative electrode current collector and reducing the risk of active ions precipitating as dendrites. On the other hand, the active ions precipitate as metals. The local volume expansion during the metal deposition process causes stress concentration. The first region 72 where the ferroelectric ceramic particles 73 are located may deform, resulting in instantaneous positive and negative charges on both sides of the separator 7 in the thickness direction. Since the active ions carry positive charges, the electric field formed by the positive charges accumulated on one side of the separator 7 repels the active ions from continuing to deposit at the stress concentration location, while the electric field formed by the negative charges accumulated on the other side (near the negative electrode sheet) attracts the active ions to deposit at this location, thereby changing the direction of dendrite growth. Taking lithium ions as an example, when lithium ions are deposited on the surface of the negative electrode, they accumulate charge, leading to localized charge concentration and the formation of a strong electric field, which in turn makes it easier for lithium ions in that area to form protruding dendrites. When the ferroelectric ceramic particles are subjected to an external electric field, they form a reverse electric field, which stops the further concentration of charge and alleviates the uneven charge distribution, thereby inhibiting the formation of dendrites. In other words, the risk of lithium ion precipitation is reduced, which can reduce the risk of lithium dendrites, thereby reducing the risk of lithium dendrites piercing the separator 7 and causing an internal short circuit in the secondary battery, thereby improving the safety performance of the secondary battery.

[0072] The ferroelectric ceramic particles 73 can also effectively reduce the current density and still regulate the dendrite growth in the application of secondary batteries at high current density.

[0073] Second, the ferroelectric ceramic particles 73 have good heat resistance and mechanical strength. When they are dispersed in the first area 72, they can improve the overall heat resistance and mechanical properties of the isolation membrane 7. As the mechanical properties of the isolation membrane 7 are improved, it is beneficial to further reduce the risk of dendrites piercing the isolation membrane 7 and causing short circuits between the positive and negative pole pieces, which can further improve the safety performance of the secondary battery. As the heat resistance of the isolation membrane 7 is improved, during the charging and discharging process of the secondary battery, it is beneficial to ensure the stability of the performance of the isolation membrane 7, thereby improving the cycle performance of the secondary battery.

[0074] Third, the porous substrate 70 is a whole-layer structure. Although it is divided into multiple regions, there may be no obvious interface between adjacent regions. Specifically, the porous substrate 70 includes a first region 72 and a second region 71, that is, along the thickness direction, the porous substrate 70 includes a second region 71 and a first region 72 arranged in sequence. The main materials of the two adjacent regions can be the same or similar materials, and there may be no obvious interface between the two adjacent regions; of course, the main materials of the two adjacent regions can also be different materials. This setting method makes the impedance between the first region 72 and the second region 71 relatively small, which is conducive to the transmission of active ions in the isolation membrane 7 and improves the dynamic performance of the secondary battery.

[0075] Fourthly, the ferroelectric ceramic particles 73 in the porous substrate 70 have good hydrophilicity and good affinity with the highly polar electrolyte, which can enhance the liquid retention capacity of the separator 7 and thus further improve the performance of the secondary battery.

[0076] In some embodiments, two second regions 71 are provided, and the first region 72 is located between the two second regions 71 , that is, the porous substrate 70 includes the second region 71 , the first region 72 , and the second region 71 arranged in sequence.

[0077] The ferroelectric ceramic particles 73 are dispersed in the first region 72, and the second region 71 is provided on both sides of the first region 72, which is equivalent to the ferroelectric ceramic particles 73 being wrapped by the second region 71; when the isolation membrane 7 is applied to the secondary battery, the ferroelectric ceramic particles 73 are not easy to contact with the positive electrode active material and / or the negative electrode active material, reducing the risk of side reactions between the ferroelectric ceramic particles 73 and the positive electrode active material and / or the negative electrode active material, reducing the loss of the positive electrode active material and / or the negative electrode active material, and ensuring the capacity performance and cycle performance of the secondary battery.

[0078] In some embodiments, the dielectric constant of the ferroelectric ceramic particles 73 is ε, and the ferroelectric ceramic particles 73 satisfy: 200≤ε≤3640.

[0079] The relatively high dielectric constant of the ferroelectric ceramic particles 73 facilitates the ferroelectric effect of the ferroelectric ceramic particles 73, significantly improving the electric field distribution at the isolation film 7. This improves the metal deposition morphology, reduces the risk of positive and negative electrode short circuits caused by dendrite formation, and enhances the safety of the secondary battery. For example, the dielectric constant of the ferroelectric ceramic particles 73 can be 200, 300, 500, 1000, 2000, 3000, 3640, or a range consisting of any two of the aforementioned values.

[0080] In some embodiments, the ferroelectric ceramic particles include one or more of a perovskite structure compound, a tungsten bronze structure compound, a pyrochlore structure compound, and a layered bismuth oxide structure compound. These materials exhibit excellent ferroelectric effects and, under the action of an external electric field, can undergo spontaneous polarization, generating a reverse electric field. This can accelerate the migration rate of active ions near the negative electrode, reduce the risk of dendrite formation, and thereby reduce the risk of dendrites piercing the separator 7 and causing an internal short circuit in the secondary battery, further improving the safety performance of the secondary battery.

[0081] Optionally, the perovskite structure compound has a tetragonal / orthorhombic / orthorhombic perovskite structure, for example, including one or more of titanates, ferrites, and niobates. The perovskite structure compound refers to an ABX3 type compound having a perovskite structure, wherein A is a cation with a larger radius, B is a cation with a smaller radius, and X is an anion; BX6 forms a regular octahedron, and BX6 is connected by a common vertex X to form a three-dimensional skeleton. A is embedded in the gaps between the octahedrons to stabilize the crystal structure.

[0082] Exemplarily, the titanate includes one or more of barium titanate BaTiO3, lead titanate PbTiO3, and strontium titanate SrTiO3, wherein the barium titanate is tetragonal barium titanate.

[0083] Exemplarily, the ferrite includes one or more of bismuth ferrite BiFeO3, lanthanum ferrite LaFeO3 and strontium ferrite SrFeO3.

[0084] Optionally, the tungsten bronze structure compound includes lead niobate PbNb2O6, barium sodium niobate Ba2NaNb5O 15 , barium strontium niobate Sr 1-x Ba x Nb2O6, lead bismuth niobate PbBiNb5O 15 and lead titanium niobate Pb3TiNb4O 15 One or more of, wherein 0<x<1. Tungsten bronze structure compounds have K x W 1-x The crystal structure of O3 is based on WO6 octahedron as a unit, with O as the vertex connecting the octahedron. This type of ceramic material has a bronze-like surface and has the characteristics of strong spontaneous polarization and high dielectric constant.

[0085] Optionally, the pyrochlore structure-like compound includes one or more of cadmium pyrotantalate (Cd2Ta2O7), lead pyroniobate (Pb2Nb2O7), cadmium pyroniobate (Cd2Nb2O7), gadolinium pyroniobate (Gd2Nb2O7), and bismuth ruthenate (Bi2Ru2O7). The general formula for the pyrochlore structure is A2B2O7, which can also be represented by A2O·B2O6. It actually has a network structure composed of interpenetrating A2O' tetrahedra of a cuprite-like structure and B2O6 octahedra of a tungsten bronze structure with shared corner vertices.

[0086] Optionally, the layered bismuth oxide structure compound includes bismuth titanate Bi4Ti3O 12 , lead bismuth niobate PbBi2Nb2O9, bismuth titanium niobate Bi3TiNbO9 and bismuth strontium titanate SrBi4Ti4O 15 One or more of the following. Layered bismuth oxide structure compounds are bismuth titanate Bi4Ti3O 12 For example, the compound is composed of (Bi2O2) 2+ The perovskite structure of the layers, Bi (located at the A position) and Ti (located at the B position) is arranged alternately, and has a good ferroelectric effect.

[0087]

[0088] In some embodiments, the volume distribution particle size Dv50 of the ferroelectric ceramic particles 73 is D, with a unit of μm, and the ferroelectric ceramic particles 73 satisfy: 0.05≤D≤5.00; optionally, 0.05≤D≤1.00.

[0089] When the volume distribution particle size of the ferroelectric ceramic particles 73 meets the above range, the ferroelectric ceramic particles 73 are not easy to clog the pores of the porous substrate 70, thereby improving the overall air permeability of the isolation membrane 7, ensuring the ion conduction channel, and improving the capacity performance and cycle performance of the secondary battery; and the particle size of the ferroelectric ceramic particles 73 will not be too large, and will be more evenly dispersed in the first region 72. The distribution density of the ferroelectric ceramic particles 73 can be relatively high, which is conducive to better exerting the ferroelectric effect; and it is conducive to reducing the thickness of the first region 72, and can reduce the overall thickness of the isolation membrane 7; and the distribution density of the ferroelectric ceramic particles 73 can be relatively high, which is conducive to better exerting the ferroelectric effect and further improving the capacity performance and cycle performance of the secondary battery.

[0090] In this application, the volume distribution particle size Dv50 of a material has a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured using a laser particle size analyzer (e.g., Master Size 3000) with reference to GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method.

[0091] In some embodiments, the porous substrate 70 may include one or more of polyolefin polymers, polyamide (PA), polyester (PLY), polysulfone (PS), and polyethersulfone (PES).

[0092] Optionally, the polyolefin polymer includes one or more of polyethylene (PE), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), polypropylene (PP), and poly-1-butene. For example, polyethylene may include medium-density polyethylene (MDPE), high-density polyethylene (HDPE), and ultra-high-density polyethylene (UHMWPE).

[0093] In some embodiments, the number average molecular weight of the polymer included in the porous substrate 70 is 5×10 4 to 5×10 6 ; Optional 1×10 5 to 1×10 6 .

[0094] When the number average molecular weight of the polymer is within the above range, it has a higher viscosity and better adhesion to the ferroelectric ceramic particles 73, and the ferroelectric ceramic particles 73 are not easily separated from the porous substrate 70. For example, the number average molecular weight of the polymer can be 5×10 4 , 8×10 4 , 1×10 5 , 3×10 5 , 5×10 5 , 1×10 6 , 5×10 6 Or a range consisting of any two of the above values.

[0095] For example, the polyethylene is a medium density polyethylene (MDPE) having a number average molecular weight of 1.5×10 5 to 2.0×10 5 .

[0096] For example, the polyethylene is high-density polyethylene (HDPE), and its number average molecular weight may be 2.0×10 5 to 4.0×10 5 .

[0097] For example, the polyethylene is ultra-high density polyethylene (UHMWPE), and its number average molecular weight may be 1.0×10 6 to 5.0×10 6 .

[0098] In this application, the number average molecular weight of a polymer has a meaning well known in the art and can be measured using equipment or methods known in the art. Specifically, the number average molecular weight of a polymer can be measured by gel permeation chromatography (GPC). Specifically, the measurement is performed using a GPC1515 instrument from Waters, USA. The sample is dissolved in tetrahydrofuran for more than 12 hours at a concentration of 4 mg / ml. The sample is filtered and prepared. The test temperature is 25°C and the test flow rate is 1 ml / min.

[0099] The inventors further discovered that when the isolation membrane 7 also satisfies at least one of the following conditions, the heat resistance, air permeability and other properties of the isolation membrane 7 can be further improved.

[0100] In some embodiments, the thickness of the second region 71 is H1, which is in μm; the thickness of the first region 72 is H2, which is in μm, and the isolation film 7 satisfies: 0.8≤H2 / 2H1≤3.0.

[0101] When the thickness of the second region 71 and the first region 72 falls within the above range, the distribution thickness of the ferroelectric ceramic particles 73 can be increased, thereby enhancing the ferroelectric effect of the ferroelectric ceramic particles 73. Optionally, 0.8 ≤ H2 / 2H1 ≤ 2. For example, H2 / 2H1 can be 0.8, 1, 1.2, 1.5, 1.8, 2.0, 2.2, 2.5, 2.8, 3.0, or a range consisting of any two of the above values.

[0102] In the present application, when the second region 71 and the first region 72 are made of different materials, there is a tiny boundary between the two, so that the thickness of the two can be measured, and the test can be carried out using equipment or methods known in the art. Specifically, the thickness of the second region 71 and the first region 72 can be measured directly by tomography, as follows: 1. Sample preparation: a. Use ceramic scissors to cut the isolation film 7 into 6mm*6mm sizes, stick it on a sample table coated with paraffin, and slightly protrude (<1mm) from the edge of the sample table; b. Spray gold on the sample for 60S; c. Set the polishing voltage and time for polishing (100min at 7.5KV for a 150um thick negative electrode); 2. Morphology analysis: Use a scanning electron microscope, move the sample position at about 50 times until it is clear, take 12 positions to mark the thickness of the second region 71 or the first region 72, and take the average value after completion to obtain the thickness of the second region 71 or the first region 72.

[0103] In some embodiments, the thickness of the isolation film 7 is H, which is expressed in μm, and the isolation film 7 satisfies: 5≤H≤25.

[0104] When the thickness of the isolation film 7 is within the above range, the mechanical properties of the isolation film 7 can be further improved. Optionally, 10≤H≤15; illustratively, the thickness of the isolation film 7 can be 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, or any two of the above ranges.

[0105] In some embodiments, the porosity P% of the isolation membrane 7 is 50≤P≤70.

[0106] When the porosity of the separator 7 is within the above range, it is beneficial to reduce ionic resistance, allowing active ions to migrate smoothly, thereby facilitating the full utilization of the capacity of the secondary battery. For example, the porosity of the separator 7 can be 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, or a range consisting of any two of the above values.

[0107] In the present application, the porosity P% of the isolation membrane 7 has a well-known meaning in the art and can be tested using equipment or methods known in the art. For example, it can be tested with reference to the standard GB / T 36363-2018.

[0108] In some embodiments, the air permeability of the isolation membrane 7 is MAP, the unit of which is s / 100 mL, and 80≤MAP≤200.

[0109] When the air permeability of the separator 7 is within the above range, it is beneficial to reduce ionic resistance, allowing active ions to migrate smoothly, thereby facilitating the full utilization of the capacity of the secondary battery. For example, the air permeability of the separator 7 can be 80 s / 100 mL, 100 s / 100 mL, 120 s / 100 mL, 150 s / 100 mL, 180 s / 100 mL, 200 s / 100 mL, or a range consisting of any two of the above values.

[0110] In this application, the air permeability of the isolation membrane 7 has a well-known meaning in the art and can be tested using equipment or methods known in the art, and can be measured using methods known in the art. For example, the test can be performed with reference to the standard GB / T36363-2018.

[0111] In some embodiments, based on the total mass of the isolation film 7 , the mass percentage of the ferroelectric ceramic particles 73 is recorded as m1%, where 1≤m1≤15.

[0112]

[0113] When the mass percentage of the ferroelectric ceramic particles 73 is within the above range, the ferroelectric effect of the entire separator 7 can be enhanced, thereby further improving the safety and cycle performance of the secondary battery. For example, the mass percentage of the ferroelectric ceramic particles 73 can be 1%, 2%, 5%, 6%, 8%, 10%, 12%, 15%, or a range consisting of any two of the above values.

[0114] In some embodiments, based on the total mass of the isolation membrane 7 , the mass percentage of the porous substrate 70 is recorded as m2%, where 85≤m2≤99.

[0115] When the mass percentage of the porous substrate 70 is within the above range, the overall mechanical strength of the separator 7 can be improved. For example, the mass percentage of the porous substrate 70 can be 85%, 88%, 89%, 90%, 92%, 94%, 95%, 96%, 98%, 99%, or a range consisting of any two of the above values.

[0116] In the present application, the mass percentage of the ferroelectric ceramic particles 73 and the porous substrate 70 can be tested using equipment and methods known in the art; specifically, a 4cm*4cm piece of the isolation membrane is cut and weighed, dissolved in nitric acid, and tested by inductively coupled plasma mass spectrometry ICP-MS, referring to HJ 766-2015 Determination of metal elements in solid waste by inductively coupled plasma mass spectrometry, to obtain the mass percentage of elements such as Ba and Ti, thereby calculating the mass percentage of the ferroelectric ceramic particles 73, and further calculating the mass percentage of the porous substrate 70.

[0117] In some embodiments, the isolation film 7 further includes a functional additive, such as an antioxidant. For example, the antioxidant is used to delay aging under the influence of light, heat, and oxygen, and can be selected from one or a combination of two or more of tris(2,4-di-tert-butylphenyl)phosphite, triphenyl phosphite, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and pentaerythritol tetrakis-β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate. When the antioxidant is a combination of two or more of the above, the ratio between them can be any ratio.

[0118] In some embodiments, fillers may be dispersed in the porous substrate 70. Furthermore, the fillers may include other inorganic particles in addition to the ferroelectric ceramic particles 73 described above.

[0119] In some embodiments, the decomposition temperature of the filler may be above 200° C., so that the filler has good thermal stability and is not easily decomposed, thereby further improving the heat resistance of the isolation membrane 7 .

[0120] The inorganic particles have the characteristics of high thermal stability and non-decomposability. Optionally, the inorganic particles include at least one of inorganic particles having ion conductivity but not storing ions and inorganic particles capable of undergoing electrochemical reactions.

[0121] The inorganic particles having ion conductivity but not storing ions include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, lithium aluminum titanium phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum lithium titanate Li x4 La y4 TiO3, lithium germanium thiophosphate Li x5 Ge y5 P z2 S w , lithium nitride Li x6 N y6 、SiS2 type glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of the following: 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7. This can further improve the ion transport characteristics of the separator 7.

[0122] Optionally, the inorganic particles capable of undergoing electrochemical reaction include at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials and lithium-titanium compounds.

[0123] In this application, the thermal shrinkage, tensile strength, and porosity of the separator 7 have well-known meanings in the art and can be measured using methods known in the art. For example, they can be tested in accordance with standard GB / T 36363-2018.

[0124] Method for preparing isolation film

[0125] In a second aspect, the present application further proposes a method for preparing an isolation membrane 7, the method comprising: S100, a mixing stage; S200, a heat treatment stage; and S300, a preparation stage of the isolation membrane 7. The method employs co-extrusion to prepare the isolation membrane 7 according to any embodiment of the first aspect of the present application. The prepared isolation membrane 7 is a monolithic structure, wherein ferroelectric ceramic particles 73 are dispersed in a first region 72 of the monolithic structure. This allows the ferroelectric ceramic particles 73 to exert a ferroelectric effect to improve the safety and cycle performance of the secondary battery. Furthermore, the porous substrate 70 protects the ferroelectric ceramic particles 73, reduces the risk of side reactions between the ferroelectric ceramic particles 73 and the active material, and improves the capacity and cycle performance of the secondary battery.

[0126] S100 may include a dry mixing stage at S110 and a wet mixing stage at S120 .

[0127] S110 specifically includes providing a supporting mixed material, the supporting mixed material comprising a first polymer. A second polymer and ferroelectric ceramic particles 73 are mixed to form a functional mixed material. The supporting mixed material is primarily used to form the second region 71 of the porous substrate 70, and the second polymer in the functional mixed material is primarily used to form the first region 72 of the porous substrate 70. The first polymer and the second polymer can be made of the same or similar polymer materials, or different polymer materials.

[0128] Optionally, the supporting mixed material may further include functional additives, such as antioxidants, nucleating agents, and the like.

[0129] For example, the antioxidant is used to delay aging under the influence of light, heat, and oxygen, and can be selected from one or a combination of two or more of tris(2,4-di-tert-butylphenyl)phosphite, triphenyl phosphite, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and pentaerythritol[tetrakis-β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. When the antioxidant is a combination of two or more of the above, the ratio between them can be any ratio.

[0130] Exemplarily, the nucleating agent is used to induce crystal nucleation, and can be one or a combination of two or more selected from terephthalic acid, azelaic acid, adipic acid and dibenzylidene sorbitol. When the nucleating agent is a combination of two or more of the above, the ratio between them is arbitrary.

[0131] As a specific example of S110, it includes: according to the set ratio, placing medium molecular weight polyethylene, a nucleating agent such as terephthalic acid, and an antioxidant such as tris(2,4-di-tert-butylphenyl)phosphite into a high-speed mixer for dispersion and mixing to form a supporting mixed material; placing ferroelectric ceramic particles 73 and high molecular weight polyethylene into a high-speed mixer for dispersion and mixing to form a functional mixed material.

[0132] In S120, in some embodiments, the support mixed material further includes a porogen. Specifically, the porogen and the first polymer are uniformly mixed and allowed to stand or stir at a temperature of 25° C. to 100° C. for 6 to 72 hours to form the support mixed material. Optionally, the stirring speed may be 700 rpm to 1200 rpm.

[0133] The functional mixed material further includes a porogen. That is, the porogen, the second polymer and the ferroelectric ceramic particles 73 are mixed uniformly and allowed to stand or stir at a temperature of 25° C. to 100° C. for 6 to 72 hours to form the functional mixed material.

[0134] Optionally, the equipment for mixing the raw materials in the supporting mixed material and the functional mixed material may be a blending equipment, such as a multi-screw extruder, a single-shaft eccentric rotor extruder or a double-shaft eccentric rotor extruder.

[0135] In some embodiments, the porogen may include a polymer porogen and / or a small molecule porogen.

[0136] Small molecule porogens are compounds with a molecular weight of less than 1000 Daltons, particularly less than 400 Daltons. Polymer porogens are compounds with a relatively larger molecular weight, such as greater than 2000 Daltons, or even up to one million Daltons.

[0137] For example, the polymer porogen may include one or more of polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), and polyvinyl alcohol (PVA).

[0138] For example, the small molecule porogen may include one or more of mineral oil, kerosene, decahydronaphthalene, sodium chloride, potassium carbonate, lithium chloride, ADC foaming agent (azodicarbonamide), and water.

[0139] The porogen is extracted from the porous substrate 70 in a subsequent step, and can create pores in the porous substrate 70 , thereby providing the porous substrate 70 with a porous structure.

[0140] In some embodiments, the weight percentage of the first polymer is 91% to 96% based on the total weight of the supporting hybrid material.

[0141] In some embodiments, the mass percentage of the nucleating agent is 0.1% to 5% based on the total mass of the supporting mixed material.

[0142] In some embodiments, the antioxidant has an amount ranging from 0.2% to 0.4% by weight based on the total weight of the supporting mixed material.

[0143] In some embodiments, the weight percentage of the porogen in the supported mixed material is 0.1% to 5% based on the total weight of the supported mixed material.

[0144] In some embodiments, the weight percentage of the second polymer is 60% to 90% based on the total weight of the functional hybrid material.

[0145] In some embodiments, the therapeutic amount percentage of the ferroelectric ceramic particles 73 is 10% to 40% based on the total mass of the functional hybrid material.

[0146] In some embodiments, the mass percentage of the porogen in the functional hybrid material is 0.1% to 5% based on the total mass of the functional hybrid material.

[0147] S200 specifically includes: heat-treating the supporting mixed material to melt the first polymer and form a supporting melt; heat-treating the functional mixed material to melt the second polymer and form a functional melt.

[0148] Melting the supporting mixed material and the functional mixed material separately is beneficial for subsequent plasticization, transportation and solidification molding.

[0149] The temperature of the heat-treated support mixed material is greater than or equal to the melting point of the first polymer, for example, 150°C to 250°C.

[0150] The temperature of the heat-treated functional mixed material is greater than or equal to the melting point of the first polymer, for example, 150°C to 250°C.

[0151] S300 specifically includes: arranging the supporting melt on at least one side of the functional melt, and co-extruding the supporting melt and the functional melt, and then stretching and solidifying them to form the isolation film 7 .

[0152] The support melt and the functional melt can be extruded through a co-extrusion die to form a multi-layer composite gel film. The multi-layer composite gel film includes the support melt, the functional melt and the support melt along its own thickness direction.

[0153] Optionally, a stretching stage may be included after forming the multilayer composite gel membrane. Specifically, the multilayer composite gel membrane may be subjected to asynchronous biaxial stretching (i.e., first transverse stretching and then longitudinal stretching, or first longitudinal stretching and then transverse stretching) or synchronous biaxial stretching (i.e., transverse stretching and longitudinal stretching are performed simultaneously).

[0154] The stretching equipment is a stretching machine, for example, an asynchronous biaxial stretching machine or a synchronous biaxial stretching film machine can be used. The transverse stretching ratio of the film is 3 to 10 times, the longitudinal stretching ratio is 3 to 10 times, and the stretching temperature is 90 to 120°C.

[0155] After stretching, a heat setting treatment is performed. During the heat setting treatment, the supporting melt and the functional melt solidify. The corresponding area after the supporting melt solidifies is mainly the second area 71, and the corresponding area after the functional melt solidifies is mainly the first area 72. When the first polymer and the second polymer are made of the same or similar materials, the main materials of the supporting melt and the functional melt are basically the same, and the isolation membrane 7 formed after the two are solidified has no obvious interface. When the first polymer and the second polymer are made of different materials, part of the first polymer in the supporting melt may enter the functional melt during the heat setting treatment, and part of the second polymer in the functional melt may enter the supporting melt during the heat setting treatment. After solidification, the interface between the functional melt and the supporting melt may not be obvious, that is, the isolation membrane 7 is a whole layer structure, and there may be no obvious interface inside it.

[0156] The heat setting temperature is 100° C. to 140° C., the heat setting pressure is 5 MPa to 20 MPa, and the heat setting time is 5 minutes to 120 minutes.

[0157] In some embodiments, the method further includes S400, a pore-forming stage; specifically, the isolation membrane 7 is sequentially subjected to organic solvent extraction and drying to provide the isolation membrane 7 with a pore structure.

[0158] The solubility of the porogen in the organic solvent is relatively higher. After the organic solvent extracts the porogen, the space originally occupied by the porogen in the isolation membrane 7 forms a pore structure, which is beneficial to improving the air permeability and ion conductivity of the isolation membrane 7.

[0159] The organic solvent may include one or more of n-hexane, acetone, chloroform, water, and ethanol.

[0160] The extraction time can be 1 min to 20 min, the drying temperature is 60° C. to 120° C., and the drying time is 2 h to 8 h.

[0161] secondary batteries

[0162] In a third aspect, the present application also provides a secondary battery.

[0163] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged after discharge to activate their active materials for continued use. Typically, a secondary battery includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator 7. The separator 7 is positioned between the positive and negative electrodes to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through.

[0164] The present application has no particular limitation on the type of secondary battery. For example, the secondary battery may be a lithium-ion battery, a sodium-ion battery, etc. In particular, the secondary battery may be a lithium-ion secondary battery.

[0165] The secondary battery described in the present application includes the separator 7 of the first aspect of the present application or the separator 7 prepared by the method of the second aspect of the embodiment of the present application, and the separator 7 is spaced between the positive electrode sheet and the negative electrode sheet.

[0166] [Positive electrode]

[0167] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and comprising a positive electrode active material. For example, the positive electrode current collector has two surfaces that oppose each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposing surfaces of the positive electrode current collector.

[0168] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material may include, but is not limited to, at least one of a lithium-containing transition metal oxide, a lithium-containing phosphate, and their respective modified compounds. Examples of the lithium transition metal oxide may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphate may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.

[0169] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Co c M d O e A f At least one of a lithium transition metal oxide and a modified compound thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M includes at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A includes at least one of N, F, S and Cl.

[0170] As an example, the positive active material for lithium ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523),LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 At least one of O2, LiFePO4, and LiMnPO4.

[0171] When the secondary battery of the present application is a sodium ion battery, the positive electrode active material may include but is not limited to at least one of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.

[0172] As an example, the positive active material for sodium ion batteries may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials, general formula X p M' q (PO4) r O x Y 3-x At least one of the materials. p M' q (PO4) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X includes H + 、Li + 、Na + , K + and NH4 +At least one of , M' is a transition metal cation, optionally at least one of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, optionally at least one of F, Cl and Br.

[0173] In the present application, the modified compounds of the above-mentioned positive electrode active materials may be the ones subjected to doping modification and / or surface coating modification on the positive electrode active materials.

[0174] In some embodiments, the positive electrode film layer may further optionally include a positive electrode conductive agent. The present application does not particularly limit the type of the positive electrode conductive agent. By way of example, the positive electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is ≤5% based on the total mass of the positive electrode film layer.

[0175] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. This application does not particularly limit the type of the positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode binder is ≤5%.

[0176] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0177] The positive electrode film layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).

[0178] [Negative electrode]

[0179] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material. For example, the negative electrode current collector has two opposing surfaces in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposing surfaces of the negative electrode current collector.

[0180] The negative electrode active material may be any negative electrode active material known in the art for use in secondary batteries. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide, and a tin alloy.

[0181] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. By way of example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5% based on the total mass of the negative electrode film layer.

[0182] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder is ≤5% based on the total mass of the negative electrode film layer.

[0183] In some embodiments, the negative electrode film layer may optionally include other additives. For example, these additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like. In some embodiments, the weight percentage of these other additives is ≤ 2% based on the total weight of the negative electrode film layer.

[0184] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0185] The negative electrode film layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring until uniformly mixed. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0186] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described herein further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode plate described herein further includes a protective layer covering the surface of the negative electrode film layer.

[0187] [Electrolyte]

[0188] During the charge and discharge process of a secondary battery, active ions are embedded and released back and forth between the positive and negative electrodes, and the electrolyte conducts the active ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and the electrolyte can be selected according to actual needs.

[0189] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.

[0190] When the secondary battery of the present application is a lithium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0191] When the secondary battery of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).

[0192] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0193] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.

[0194] In some embodiments, the positive electrode sheet, the separator 7 and the negative electrode sheet can be made into an electrode assembly through a winding process and / or a lamination process.

[0195] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0196] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0197] The present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. FIG2 shows a secondary battery 5 with a square structure as an example.

[0198] In some embodiments, as shown in FIG3 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator 7 can be formed into an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.

[0199] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, separator 7, negative electrode sheet, and electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, separator 7, and negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process. The electrode assembly is placed in an outer packaging, dried, and then injected with electrolyte. The secondary battery is obtained through vacuum packaging, static standing, formation, and shaping processes.

[0200] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.

[0201] Figure 4 is a schematic diagram of an exemplary battery module 4. As shown in Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured using fasteners.

[0202] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of secondary batteries 5 are accommodated in the accommodation space.

[0203] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0204] Figures 5 and 6 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 5 and 6, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 may be arranged in any manner within the battery box.

[0205] Electrical devices

[0206] The fourth aspect of the embodiment of the present application provides an electric device, which includes at least one of the secondary battery, battery module or battery pack of the present application. The secondary battery, battery module or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0207] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0208] Figure 7 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.

[0209] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.

[0210] Example

[0211] The following examples describe the present disclosure in more detail. These examples are intended to be illustrative only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing. The instruments used in the examples are commercially available.

[0212] Example 1 Preparation of lithium-ion battery

[0213] Preparation of isolation membrane

[0214] (1) Inorganic tetragonal barium titanate BTO (particle size of 500 nm) and 1.6 million molecular weight ultra-high molecular weight polyethylene were fully dispersed in a high-pressure mixer at a mass ratio of 15:85 to form a first group of mixed materials;

[0215] The second group of mixed materials is prepared by fully dispersing 1.6 million molecular weight ultra-high molecular weight polyethylene, a nucleating agent such as terephthalic acid, and an antioxidant such as tris(2,4-di-tert-butylphenyl)phosphite in a mass ratio of 99:0.7:0.3 in a high-pressure mixer;

[0216] (2) Adding the porogen PVP to each of the two mixed materials obtained in step (1) to a PVP content of 1% of each mixed material. After thorough stirring and uniform dispersion, the mixture was allowed to stand at room temperature for 24 hours to obtain a support mixed material and a functional mixed material.

[0217] (3) The support mixed material and the functional mixed material obtained in step (2) are melt-blended and plasticized at 200° C. through an eccentric rotor extruder and transported into a three-layer co-extrusion die, wherein the support mixed material enters the outer two sides and the functional mixed material enters the inner side, and after casting and cooling, a three-layer composite gel film is formed;

[0218] (4) stretching the three-layer composite gel film obtained in step (3) on a synchronous biaxial stretching machine with a stretching ratio of 5×5 and a stretching temperature of 118° C., and then heat-setting at 130° C., a pressure of 10 MPa, and a time of 60 min;

[0219] (5) The biaxially oriented film obtained in step (4) is subjected to dichloromethane ultrasonic extraction, alcohol soaking, deionized water rinsing, and drying to obtain an isolation film.

[0220] Preparation of positive electrode

[0221] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.

[0222] The positive electrode active material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) in a mass ratio of 96.2:2.7:1.1 to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through processes such as drying, cold pressing, slitting, and cutting.

[0223] Preparation of negative electrode sheet

[0224] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.

[0225] Natural graphite, the negative electrode active material, is mixed with Super P (a conductive agent), CMC (a thickener), and SBR (a binder) in deionized water to create a negative electrode slurry. The solids content is 30% by weight, and the mass ratio of graphite, Super P, CMC, and SBR (a binder) is 80:15:3:2. The negative electrode slurry is coated onto a current collector copper foil and dried at 85°C. The negative electrode sheet is then cold-pressed, trimmed, cut, and slit, and then dried at 120°C under vacuum for 12 hours.

[0226] Preparation of electrolyte

[0227] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate EC and diethyl carbonate DMC are mixed in a volume ratio of 1:1 to obtain an electrolyte solvent, and then lithium salt and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.

[0228] Preparation of secondary batteries

[0229] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to obtain an electrode assembly; the electrode assembly is placed in an outer package, dried, and then injected with electrolyte. After vacuum packaging, standing, formation, shaping and other processes, a lithium-ion battery is obtained.

[0230] Comparative Example 1

[0231] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the ferroelectric ceramic particles were adjusted to silicon oxide SiO2.

[0232] Comparative Example 2

[0233] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 is that the steps for preparing the isolation membrane are as follows:

[0234] Ultra-high molecular weight polyethylene with a molecular weight of 1.6 million was selected as the porous substrate, and was cut into appropriate sizes according to the sizes of the positive electrode sheet and the negative electrode sheet.

[0235] Inorganic particles of tetragonal barium titanate BTO (particle size of 500nm) and 1.6 million molecular weight ultra-high molecular weight polyethylene are mixed in a mass ratio of 15:85 and stirred in a vacuum mixer until the system becomes a uniform barium titanate slurry. The barium titanate slurry is coated on both surfaces of a porous substrate. After drying at 110°C, the barium titanate slurry is solidified into a coating on the porous substrate.

[0236] Example 2

[0237] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the material of the ferroelectric ceramic particles was adjusted in Examples 2-1 and 2-3.

[0238] Example 3

[0239] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the particle size of the ferroelectric ceramic particles was adjusted in Examples 3-1 and 3-3.

[0240] Example 4

[0241] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the thickness of the isolation film was adjusted in Examples 4-1 and 4-4.

[0242] Example 5

[0243] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the thicknesses of the first region and the second region in the isolation membrane were adjusted in Examples 5-1 to 5-3.

[0244] Example 6

[0245] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the mass percentage of the ferroelectric ceramic particles in the isolation film was adjusted in Examples 6-1 to 6-3.

[0246] Example 7

[0247] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the porosity of the separator was adjusted in Examples 7-1 to 7-3.

[0248] Example 8

[0249] A lithium-ion battery was prepared using a method similar to that of Example 1. Unlike Example 1, a double-layer co-extrusion technique was used in Example 8, and the separator comprised a first region and a second region.

[0250] The parameters of the embodiments and comparative examples are shown in Table 1 and Table 2.

[0251] Test section

[0252] 1. Puncture strength test of isolation film

[0253] According to the national standard GB / T 36363-2018 Polyolefin separators for lithium-ion batteries, the lithium battery separator is flattened in a fixture and clamped. It is punctured at a rate of (100+10) mm / min. After completion, the sample is removed and the thickness is tested at four points around the pinhole in accordance with the provisions of GB / T6672-2001. The average value is taken and the puncture strength is calculated.

[0254] 2. Isolation film internal resistance test

[0255] The test was conducted in accordance with the standard of GB / T36363-2018. Specific test steps: Cut 4 pieces of diaphragms that match the test mold, place them in an electrolyte with a volume ratio of 1:1:1 of 1mol / L lithium hexafluorophosphate, EC, EMC, and DEC, keep them sealed and soaked for 2 hours, inject the electrolyte into the resistance test mold, place one layer of diaphragm in turn, test its AC impedance, then place another layer of diaphragm, test its AC impedance, until 4 layers are placed, and obtain the AC impedance R1, R2, R3, and R4 respectively. Plot the graph with the number of diaphragm layers as the horizontal axis and the AC impedance as the vertical axis. When the linear fit is greater than 99%, the slope is the internal resistance of the diaphragm.

[0256] 3. Discharge rate test of secondary batteries

[0257] 1) A discharge rate test was conducted using a button cell battery. The positive electrode of the button cell battery used lithium iron phosphate, wherein the ratio of lithium iron phosphate: conductive carbon black: PVDF binder was 8:1:1, the negative electrode used a lithium sheet, the electrolyte used 1M LiFSI / DME, and the separator used was the separator of the embodiment and comparative example.

[0258] 2) Charging Conditions: The battery was charged at room temperature using the constant current-constant voltage (CC-CV) mode. First, the battery was charged in the constant current mode at various current rates (0.5 / 1 / 2C) until the voltage reached 3.65V. The battery was then switched to the constant voltage mode with a cutoff current of 0.05C to fully charge.

[0259] 3) Discharge conditions: Discharge in constant current mode at a discharge rate of 0.33C to 2.5V and cycle 100 times.

[0260] 4) Calculate and record the coulombic efficiency (discharge capacity / charge capacity*100%) at different charge rates after 100 cycles.

[0261] Test results

[0262] Table 1

[0263] Table 2

[0264] The isolation membrane of Comparative Example 1 adopts three-layer co-extrusion and adds silicon oxide SiO2 filler, which can improve the heat resistance and mechanical properties of the isolation membrane and reduce the risk of lithium dendrites piercing the isolation membrane; however, the amount of lithium dendrites generated is still large, resulting in poor rate performance of the lithium-ion battery.

[0265] The embodiment of the present application uses three-layer co-extrusion to add tetragonal barium titanate BTO to the middle part of the isolation membrane, thereby reducing the side reactions caused by the contact between the tetragonal barium titanate BTO and the electrolyte, etc., while reducing the risk of active ions precipitating as dendrites, thereby improving the rate performance of the lithium-ion battery. As shown in Figures 8 and 9, the middle part of the isolation membrane of Example 1 is filled with tetragonal barium titanate BTO. Of course, the embodiment of the present application can also add tetragonal barium titanate BTO to the isolation membrane through double-layer co-extrusion technology to improve the rate performance of the lithium-ion battery.

[0266] In Comparative Example 2, tetragonal barium titanate (BTO) was applied to the porous substrate of the separator by a coating method. Although the tetragonal barium titanate (BTO) can generate a reverse electric field and improve the growth of dendrites, direct contact between the tetragonal barium titanate (BTO) and the electrolyte may cause side reactions between the tetragonal barium titanate (BTO) and the electrolyte, reducing the regulating effect of the tetragonal barium titanate (BTO), which is not conducive to the rate performance of the lithium-ion battery. As shown in Figure 10, in the layer structure of the separator of Comparative Example 2, the boundaries between adjacent layers are clear and there is a certain gap, which poses a risk of layer shedding. In contrast, the connection between the layers in the separator of Example 1 is tighter and the bonding force is stronger. The tetragonal barium titanate (BTO) is evenly dispersed in the separator, which is conducive to the uniform function of the tetragonal barium titanate (BTO).

[0267] Examples 2-1 to 2-3 all have an excellent effect of reducing dendrite formation by adjusting the material of the ferroelectric ceramic particles. When the particle size of the ferroelectric ceramic particles in Examples 3-1 to 3-3 meets the range of 0.05 to 5.00, the permeability of the isolation membrane can be improved, the transmission rate of lithium ions can be increased, and the performance of the lithium-ion battery can be improved. Examples 4-1 to 4-4 and Examples 5-1 to 5-3 adjust the thickness of the isolation membrane, the first region, and the second region to adjust the distribution of the ferroelectric ceramic particles, thereby adjusting the magnitude of the ferroelectric effect exerted by the ferroelectric ceramic particles.

[0268] By adjusting the mass percentage of ferroelectric ceramic particles in the separator, Examples 6-1 to 6-3 can modulate the ferroelectric effect exerted by the ferroelectric ceramic particles. By adjusting the porosity, Examples 7-1 to 7-3 can improve the permeability of the separator, thereby increasing the lithium ion transmission rate and improving the performance of the lithium-ion battery.

[0269] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.

Claims

1. An isolation film, comprising a porous substrate and ferroelectric ceramic particles, wherein the porous substrate comprises a first region and a second region arranged along a thickness direction of the isolation film, and the ferroelectric ceramic particles are dispersed in the first region.

2. The isolation film according to claim 1, wherein: The dielectric constant of the ferroelectric ceramic particles is ε, and the ferroelectric ceramic particles satisfy: 200≤ε≤3640.

3. The isolation film according to claim 1 or 2, wherein: The ferroelectric ceramic particles include one or more of a perovskite structure compound, a tungsten bronze structure compound, a pyrochlore structure compound and a layered bismuth oxide structure compound; Optionally, The perovskite structure compound includes one or more of titanate, ferrite and niobate; Further optionally, the titanate includes one or more of barium titanate BaTiO3, lead titanate PbTiO3 and strontium titanate SrTiO3; the ferrite includes one or more of bismuth ferrite BiFeO3, lanthanum ferrite LaFeO3 and strontium ferrite SrFeO3; Optionally, The tungsten bronze structure compounds include lead niobate PbNb2O6, barium sodium niobate Ba2NaNb5O 15 、Barium strontium niobate Sr 1-x Ba x Nb2O6, lead bismuth niobate PbBiNb5O 15 and lead titanium niobate Pb3TiNb4O 15 One or more of, wherein 0<x<1; Optionally, The pyrochlore structure compound includes one or more of cadmium pyrotantalate Cd2Ta2O7, lead pyroniobate Pb2Nb2O7, cadmium pyroniobate Cd2Nb2O7, gadolinium pyroniobate Gd2Nb2O7 and bismuth ruthenate Bi2Ru2O7; Optionally, The layered bismuth oxide structure compound includes bismuth titanate Bi4Ti3O 12 , lead bismuth niobate PbBi2Nb2O9, bismuth titanium niobate Bi3TiNbO9 and bismuth strontium titanate SrBi4Ti4O 15 One or more of .

4. The separator according to any one of claims 1 to 3, wherein: The volume distribution particle size Dv50 of the ferroelectric ceramic particles is D, and its unit is μm. The ferroelectric ceramic particles satisfy: 0.05≤D≤5.00; optionally, 0.05≤D≤1.

00.

5. The separator according to any one of claims 1 to 4, wherein: The porous substrate comprises one or more of polyolefin polymers, polyamide, polyester, polysulfone and polyethersulfone; Optionally, the polyolefin polymer includes one or more of polyethylene, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl chloride, polypropylene and poly-1-butene.

6. The separator according to any one of claims 1 to 5, wherein: The porous substrate comprises a polymer, wherein the number average molecular weight of the polymer is 5×10 4 Up to 5×10 6 ; Optional 1×10 5 Up to 1×10 6 .

7. The separator according to any one of claims 1 to 6, wherein: The thickness of the second region is H1, and its unit is μm; The thickness of the first region is H2, in μm. The isolation film satisfies: 0.8≤H2 / 2H1≤3; optionally, 0.8≤H2 / 2H1≤2; Optionally, 2.5≤H1≤4.5; and / or 3.5≤H2≤7.

5.

8. The separator according to any one of claims 1 to 7, wherein: The thickness of the isolation film is H, the unit of which is μm, and the isolation film satisfies: 5≤H≤25; optionally, 10≤H≤15.

9. The separator according to any one of claims 1 to 8, wherein: The porosity of the isolation membrane is P%, 50≤P≤70; and / or The air permeability of the isolation membrane is MAP, the unit of which is s / 100mL, and 80≤MAP≤200.

10. The separator according to any one of claims 1 to 9, wherein: Based on the total mass of the isolation film, the mass percentage of the ferroelectric ceramic particles is recorded as m1%, 1≤m1≤15; and / or Based on the total mass of the isolation membrane, the mass percentage of the porous substrate is recorded as m2%, 85≤m2≤99.

11. The separator according to any one of claims 1 to 10, wherein: The number of the second regions is two, and the first region is located between the two second regions.

12. A method for preparing an isolation film, comprising: providing a supported hybrid material, the supported hybrid material comprising a first polymer; mixing a second polymer and ferroelectric ceramic particles into a functional hybrid material; thermally treating the supported mixed material to melt the first polymer and form a supported melt; heat treating the functional mixed material to melt the second polymer and form a functional melt; The supporting melt is arranged on at least one side of the functional melt, and the supporting melt and the functional melt are co-extruded, stretched, and solidified to form a separation film. 13 . A secondary battery comprising the separator according to claim 1 or the separator prepared by the method according to claim 12 .

14. An electric device comprising the secondary battery according to claim 13.

Citation Information

Cited By

  • Method for preparing coal-based hard carbon by enhancing coal oxidation reaction activity

    CN120757102A